DISIPLIN DAN KESEJAHTERAAN KERJA TERHADAP KINERJA DOSEN PADA SEKOLAH TINGGI ILMU ADMINISTRASI KOTA BENGKULU - Ratnawili Ratnawili; Yalmita Sari ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
The purpose of this study was to determine the effect of Discipline and Work welfare on Lecturer Performance in Bengkulu City Administration College. This research method uses quantitative research, the population in this study are all lecturers of Bengkulu City Administration College with a total of 38 people, the sample used is Random Sampling which means by random sampling. Data collection techniques using observation, questionnaires. The analysis technique used is multiple linear regression test, coefficient of determination, hypothesis testing (t test and f test). The results showed that discipline had a significant effect on lecturer performance at the Bengkulu City College of Administrative Sciences. This means that Ho is rejected and Ha is accepted. Work Welfare has a significant effect on the Performance of Bengkulu City Administration College of Higher Education, this is evidenced by the results of the t test showing the value of t> t table (3.021> 1.689) and (sig a = 0.005 <0.050), this means that Ho is rejected and Ha is accepted. Discipline (X1), Work Welfare (X2), together affect the Performance of Lecturers (Y) in Bengkulu City Administrative College, this is evidenced by the F test showing the value of Fcount> Ftable (10.068> 3.27) and (sig a = 0,000 <0.050). This means that Ho is rejected and Ha is accepted. Based on the correlation coefficient test, it is obtained the value of R = 0.604 and the coefficient of determination obtained the value of R2 = 0.365 value has the meaning that Discipline (X1), Work Welfare (X2), contributes a significant influence of 0.365 or 36.5% on Lecturer Performance (Y) In Bengkulu City College of Administrative Sciences. While the remaining 63.5 or 63.5% is influenced by other variables not included in this study.Â Keywords: Discipline, Job Welfare, and Lecturer Performance